First casualty: the untold story of the CIA mission to avenge 9/11 - Harnden, Toby (Little, Brown and Company)
Zero hour -- Blue sky -- Third option -- Showtime -- Kill box -- Talisman -- Two Cadillacs -- Wild thing -- Devil's water -- The fort -- Goat rodeo -- Not surrendered -- The Irishman -- Pink house -- Trojan horse -- Cleared hot -- Absolutely wrong -- Yeah, baby! -- Lucky boots -- No secrets -- Tomorrowland -- Days of thunder.